2010
DOI: 10.1351/pac-con-09-10-30
|View full text |Cite
|
Sign up to set email alerts
|

Dust particles in low-pressure plasmas: Formation and induced phenomena

Abstract: Formation of dust particles is a common mechanism in low-pressure plasmas. These big particles (in comparison with other plasma species) are sometimes the desired final products of the process, but they may also constitute a severe drawback in certain contexts. In either situation, it is necessary to understand growth mechanisms well, in order to control or avoid dust particle formation. One of the problems that has to be overcome is that dust particle growth is usually a continuous mechanism: once started, it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 49 publications
1
20
0
Order By: Relevance
“…In laboratory reactors, there are many methods to create dust particles, mainly using reactive gases [8][9][10][11][12][13][14]o r material sputtering [15][16][17][18]. In the present work, material sputtering is used to grow a high density of sub-micron dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…In laboratory reactors, there are many methods to create dust particles, mainly using reactive gases [8][9][10][11][12][13][14]o r material sputtering [15][16][17][18]. In the present work, material sputtering is used to grow a high density of sub-micron dust particles.…”
Section: Introductionmentioning
confidence: 99%
“…Dust particles can be grown inside a plasma by gas phase reactions [1][2][3] that lead to high densities of submicron dust particles. These particles acquire a negative charge and when the global charge they represent is no more negligible compared with the electron density, a wide variety of low frequency instabilities are observed.…”
mentioning
confidence: 99%
“…Taking into account the transient nature of the shoulder and other reports [101][102][103] one can explain the formation of the second generation as follows. At first a void forms inside the discharge.…”
Section: Investigation Of the 1st Discharge Cyclementioning
confidence: 99%
“…It has indeed been shown that nanoparticles only nucleate in areas of the discharge with a sufficiently low number 200 nm density of nanoparticles, like voids, i.e. particle free volumes inside the discharge [101][102][103]. A reduced nucleation rate leads to a lower number density of nanoparticles in the discharge.…”
Section: Cyclic Behaviour Of the Dischargementioning
confidence: 99%